Behavioral Accounting and the Humanization of Financial Practices in MSMEs - Retno Cahyaningati; Deni Juliasari; Selvia Roos Ana (AKRUAL: JURNAL AKUNTANSI, 2026)
Introduction/Main Objectives: This research investigates the implementation of behavioral accounting in micro, small, and medium-sized enterprises (MSMEs) in Lumajang Regency, Indonesia, highlighting its function as a behavioral mechanism that amalgamates financial management with ethical, motivational, and social aspects. Methods: Employing a qualitative descriptive methodology, data were gathered via in-depth interviews, participatory observations, and documentation from government officials, MSME proprietors, field facilitators, and accounting scholars. The analysis utilized a thematic coding methodology to discern patterns of motivation, risk perception, and ethical awareness that impact accounting behavior and business productivity. Results/Findings: The results show that human behavior, not formal financial systems, is what drives MSMEs to use accounting practices the most. Three main factors motivation, risk perception, and ethics came to light as the most important ones that affect adaptive and reflective accounting behavior. These dimensions together create a pattern of behavior that boosts productivity not only by being financially efficient, but also by being morally disciplined and socially responsible. Conclusions: The research illustrates that behavioral accounting can function as a conduit between formal economic frameworks and sociocultural contexts, thereby advancing the theoretical evolution of behavioral-humanistic accounting. In practice, the study underscores the significance of behavior-based accounting education that incorporates moral and social consciousness into MSME empowerment initiatives. In theory, it broadens the application of behavioral accounting from corporate settings to community-based enterprises, supporting the humanistic perspective that sustainable productivity arises from ethical conduct and reflective awareness rather than solely from financial rationality.